Synthesis of Salicylic Acid Based Mixed Ligand Complexes: Their Protein Binding Affinities and Antimicrobial Activities - Aggarwal, Nidhi; Mehtab, Sameena; Maji, Suman (Asian Journal of Chemistry, 2017)
Present study is based upon synthesis, characterization, bovine serum albumin binding interactions and antimicrobial studies of mixed ligand complexes of zinc with salicylic acid or 3,5-dinitrosalicylic acid as primary ligand and 1,10-phenanthroline or 2,2-bipyridyl as secondary ligand. These complexes are characterized by UV-visible, IR and elemental analysis to determine the mode of binding between metal and ligand. The interaction of these complexes with protein molecules were studied by determining the binding constants from interaction with bovine serum albumin using UV-visible titration techniques. The antimicrobial activities of these complexes have been tested against bacteria and fungi. It has been observed that the above mentioned complexes show considerable antimicrobial activity compared to the free ligands.